2017
DOI: 10.1089/cyber.2016.0363
|View full text |Cite
|
Sign up to set email alerts
|

Socially Interactive and Passive Technologies Enhance Friendship Quality: An Investigation of the Mediating Roles of Online and Offline Self-Disclosure

Abstract: Previous studies indicate that characteristics of social-based technologies (STs) stimulate the sharing of intimate information online, which in turn enhances the quality of friendships. In addition, intimate online self-disclosure has been positively associated with offline self-disclosure. One objective of the current study was to combine the literature and test a model which postulates that STs use stimulates online self-disclosure which facilitates offline self-disclosure and, thereby, enhances the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 30 publications
5
20
0
2
Order By: Relevance
“…These significant relationships were found for various well-being outcomes (such as subjective well-being well-being), and for various types of self-presentation (such as breadth of self-presentation, idealized self-presentation). Similar mediation effects were found for variables like perceived social closeness, social connectedness, positive feedback, bridging and bonding social capital, and depth of face-to-face disclosures, which underscores the important role of reinforcement by others 7,10,15,28,31,33 . Here, the general line suggests that peers have an important role in determining outcomes.…”
Section: Mediatorssupporting
confidence: 65%
“…These significant relationships were found for various well-being outcomes (such as subjective well-being well-being), and for various types of self-presentation (such as breadth of self-presentation, idealized self-presentation). Similar mediation effects were found for variables like perceived social closeness, social connectedness, positive feedback, bridging and bonding social capital, and depth of face-to-face disclosures, which underscores the important role of reinforcement by others 7,10,15,28,31,33 . Here, the general line suggests that peers have an important role in determining outcomes.…”
Section: Mediatorssupporting
confidence: 65%
“…Thematic analysis findings may contribute to building a theory behind why the effect was only small sized as it revealed mixed feelings regarding perceived connectivity, where some participants felt more socially connected offline, while others expressed concerns over the loss of online SC to peers during abstinence, demonstrating individual differences in perceived SC. Perhaps those who experienced lower SC without SM used these platforms to overcompensate for perceived lack of offline connectedness, which may explain the mixed feelings in perceived connectivity as a result of abstinence [ 75 , 76 ]. Although individuals find the connectivity aspect of SM appealing [ 30 , 35 ], prior research suggests that people perceive offline connections as more important than online connections [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to physical activity, young people experiencing poorer psychological health may turn to internet-based services for information seeking and support, and bi-directional relationships are probable. It has also been suggested that the connection and relationship experiences on online networking may not offer equivalent protective benefits that can be achieved through face-to-face friendships and networking [56]. Given the substantial time spent using technology daily and the increasing social activities that now occur online, the health effects of screen use are of current and future public health interest.…”
Section: Discussionmentioning
confidence: 99%